2020
DOI: 10.1155/2020/9617303
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Vastus Lateralis Rupture and Repair Using Suture Anchor Technique

Abstract: Introduction. This is a case report of an isolated vastus lateralis rupture identified by MRI and treated successfully with surgical repair. Case Presentation. A 50-year-old male recreational weightlifter who sustained an isolated vastus lateralis rupture while dead lifting and underwent surgical repair using a suture anchor fixation. Conclusion. An isolated vastus lateralis rupture is a rare injury that may be successfully treated with surgical repair allowing return to preinjury activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The patient remains injuryfree and endorses no pain or limitations relating to his quad injury. n Steven Elicegui, BS 1 Mark Stovak, MD 1 Jordan Dobrich, BS, MBA 1 John Hodges, DPT 2 Vijay Sekhon, MD 3 Christopher Dolan, MD 1,4 1 University of Nevada, Reno School of Medicine, Reno, Nevada 2 Nevada Physical Therapy, Reno, Nevada 3 Reno Diagnostics Center, Reno, Nevada 4 Great Basin Orthopaedics, Reno, Nevada E-mail address for S. Elicegui selicegui@med.unr.edu…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient remains injuryfree and endorses no pain or limitations relating to his quad injury. n Steven Elicegui, BS 1 Mark Stovak, MD 1 Jordan Dobrich, BS, MBA 1 John Hodges, DPT 2 Vijay Sekhon, MD 3 Christopher Dolan, MD 1,4 1 University of Nevada, Reno School of Medicine, Reno, Nevada 2 Nevada Physical Therapy, Reno, Nevada 3 Reno Diagnostics Center, Reno, Nevada 4 Great Basin Orthopaedics, Reno, Nevada E-mail address for S. Elicegui selicegui@med.unr.edu…”
Section: Discussionmentioning
confidence: 99%
“…C urrent literature involving isolated quadriceps muscle tears demonstrates that they typically occur distally through the tendon or avulsion of the tendon at its insertion 3,4,20 . These tears are a result of overstressing the muscle, while tears of the muscle belly occur during sharp penetrative traumas or overstretching 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al 3 reported the case of a 50-year-old male powerlifter who sustained an injury to his left thigh and heard a loud pop while deadlifting 180 kg. He reported immediate swelling and a palpable defect over the lateral quadriceps.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported cases describe VL injuries resulting from rapid eccentric muscle contraction while lifting a heavy load sufficient to avulse the tendon from its bony insertion. [2][3][4] However, in the first case, there was no known single traumatic injury other than mild snowboarding falls that were not incapacitating. The second patient did report an acute injury, but it occurred after a football collision.…”
Section: Discussionmentioning
confidence: 99%